PENGARUH PELAYANAN CUSTOMER SERVICE TERHADAP PENINGKATAN CITRA PERUSAHAAN: STUDI KORELASIONAL PADA PT. ACE HARDWARE INDONESIA, TBK. DI LENMARC MALL SURABAYA - Giastanti, Meta; Hamim, Hamim; Pratiwi, Ni Made Ida (representamen, 2018)
Service is very important thing take precedence in the company of retail. The one that appliedis the service excellence. Basically, satisfaction and comfort comes from service excellence tocustomers. All parties who were in the company should be involved in providing service excellence.Provide service excellence to customers with good attitude, can increase the positive corporate image.This research aims to know there is not a relationship of service Customer Service against theinfluence of the improvement of corporate image in PT. ACE Hardware Indonesia, Tbk. at LenmarcMall Surabaya. The research method use is the method of quantitative research with correlationapproach. The sample use as many as 100 customers/ respondents who came to shopping at PT. ACEHardware Indonesia, Tbk. Lenmarc Mall Surabaya. Sampling technique used was Quota Samplingwith method of data collection is the spread of questionnaire. Data analysis use is simple correlationanalysis, t test and simple linear regression analysis with manual calculation. Based on the hypothesistest result where NH>NT (9,8217>1,9842) there was significant influence between service ofCustomer Service towards the improvement of the corporate image. And from the results ofcorrelation test of the 0,759 correation approach +1 with sig. 0,000>0,05 that there is a significantinfluence on relations between the service of Customer service towards the improvement of thecorporate image.Keywords: Service, Customer Service, Corporate Image.